Partisipasi Masyarakat untuk Penguatan Wisata Sungai Berbasis Kewirausahaan Kreatif dalam Disain Kawasan Sungai Jawi Pontianak - Zairin Zain; Affrilyno; Hamdil Khaliesh; Ivan Adiel Abednego (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
As part of the city of Pontianak, Sungai Jawi Village is a settlement that grows along the river flowing into the Kapuas River. The potential as a growth path in the past has caused the settlement of Sungai Jawi Village to develop quite rapidly. Physical and socio-economic problems in the Sungai Jawi Settlement Area are commonly found as urban villages. Participation in the community's contribution is actively involved in problem-solving discussions and identification of potentials in obtaining the formulation of the spatial concept of creative entrepreneurship in Sungai Jawi Village. The formulation of this spatial concept is used in the design to accommodate the economic activities of the local population. The program's sustainability in creative entrepreneurship by empowering local communities is essential through collaboration in improvement and assistance with related parties, including the Pontianak city government and the private sector. In implementing the design of the spatial concept of creative entrepreneurship, Sungai Jawi Village is expected to become a river tourism destination by offering the community's potential in creative entrepreneurship. This action can inspire people in these settlements and other areas located by the river to start a similar settlement concept. This program has produced several planning documents by turning the Jawi River into a binding element for tourism areas to foster creative entrepreneurship.